2012
DOI: 10.9790/0853-0162730
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Study of Prophylactic Use of Umbilical Vein Oxytocin in The Management of Third Stage of Labor.

Abstract: Abstract-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…(Table 5) Kore et al [12] found significant less blood loss and duration of third stage of labour with intraumblical injection of 10 units of oxytocin than 10 units of IV oxytocin [12]. Manhas et al [13] also found significant less blood loss and duration of third stage of labour with intraumblical injection of 20 units of oxytocin than 2 mg of methylergometrine IV [13]. While Ojha et al [14] found almost no difference in duration of third stage of labour with intraumblical injection of 10 units of oxytocin than 10 units of IM oxytocin and blood loss in third stage was more with intraumblical oxytocin [14].…”
Section: Discussionmentioning
confidence: 99%
“…(Table 5) Kore et al [12] found significant less blood loss and duration of third stage of labour with intraumblical injection of 10 units of oxytocin than 10 units of IV oxytocin [12]. Manhas et al [13] also found significant less blood loss and duration of third stage of labour with intraumblical injection of 20 units of oxytocin than 2 mg of methylergometrine IV [13]. While Ojha et al [14] found almost no difference in duration of third stage of labour with intraumblical injection of 10 units of oxytocin than 10 units of IM oxytocin and blood loss in third stage was more with intraumblical oxytocin [14].…”
Section: Discussionmentioning
confidence: 99%
“…A period between birth of fetus and delivery of the placenta along with membranes is known as third-stage of labor. [1][2][3] Many times third stage may cause serious complication for both mother and newborn. [4,5] If duration of the third stage exceeds 30 min, it may result in serious risk of postpartum hemorrhage, puerperal infection, and retained placenta.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] If duration of the third stage exceeds 30 min, it may result in serious risk of postpartum hemorrhage, puerperal infection, and retained placenta. [2] In developing countries, about 25% of maternal mortality is caused by postpartum hemorrhage. [2,6] Retention of the placenta complicates approximately 0.1-3.3% of cases © 2019 IJNR | Published by Innovational Publishers globally, and the risk of recurrence may be as high as 16-23%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manhas A et al conducted a study in which Group 1 received umbilical vein injection of oxytocin. 10 Group 2 received intraumbilical vein saline injection while subjects in group 3 were managed with systemic methylergometrine, 0.2mg intravenous at the delivery of anterior shoulder. …”
mentioning
confidence: 99%